Application of the Search Solve Create Share Learning Model to Metacognitive Awareness and Learning Outcomes - Kusmiyati, Kusmiyati; Merta, I Wayan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to determine metacognitive awareness and learning outcomes through the search, solve, create and share (SSCS) learning model. This research was conducted on second-semester Biology Education Study Program students who took the Introduction to Education course. Metacognitive awareness data was collected using a modified questionnaire from the Metacognitive Awareness Inventory, then analysed qualitatively with four categories from not yet developed to very well developed. Learning outcome data is collected through tests and then analysed qualitatively, using five categories: very poor to very good. The metacognitive awareness results were dominated by students in the very well-developed category, as many as 48 people (96%), while the learning outcomes were dominated by students in the good category, as many as 24 people (48%). In conclusion, through the SSCS learning model, students can: (1). Manage their cognitive abilities and overcome their shortcomings very well; (2). Building independence, critical thinking, creativity, and self-confidence improves learning outcomes.